2009
DOI: 10.1080/11038120903082260
|View full text |Cite
|
Sign up to set email alerts
|

Vocational intervention based on the Model of Human Occupation: A review of evidence

Abstract: Work is a growing concern in disability and rehabilitation fields. Specific evidence related to occupational therapy in the area of vocational rehabilitation is somewhat limited. With increased demands for occupation-focused, evidence-based, and theory-informed practice, this review aims to use clinically relevant questions to organize and synthesize evidence regarding work-related interventions specifically related to an occupation-focused theory, the Model of Human Occupation. A total of 45 published works r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Thus, the findings in the present study increase the knowledge about actions that can be important in making sustainable improvements guided by an OT model of practice. In addition, and in line with other studies of the implementation of theories or models in OT, it was found that the implementation enhances occupational therapists' attempts to undertake evidencebased clinical interventions, and increase the occupation focus in practice as well the client-centredness (17)(18)(19)30). However, the findings add to existing knowledge by illustrating how implementations relating to evidence-based interventions, occupation focus, and client-centredness can become connected with sustainability.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, the findings in the present study increase the knowledge about actions that can be important in making sustainable improvements guided by an OT model of practice. In addition, and in line with other studies of the implementation of theories or models in OT, it was found that the implementation enhances occupational therapists' attempts to undertake evidencebased clinical interventions, and increase the occupation focus in practice as well the client-centredness (17)(18)(19)30). However, the findings add to existing knowledge by illustrating how implementations relating to evidence-based interventions, occupation focus, and client-centredness can become connected with sustainability.…”
Section: Discussionsupporting
confidence: 66%
“…Together, these difficulties provide important reasons for occupational therapists working in health-care settings to make the intervention process in their daily practice evidence-based. The implementation of evidence, including models of practice, has been found to be valuable, as it gives a strong foundation for OT practice (28,30). However, it is known that sustainable implementation of evidence in OT, as in other areas, is challenging and takes time (6,12,18).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the present study correlate with those in the literature, in confirming that knowledge translation is a complex process for which there is no easy solution (Grol and Wensing, ; Grol et al, ; Lencucha et al, ; Metzler and Metz, ; Stergiou‐Kita, ). It is clear that for this group of OTs, as in the literature, there are many barriers to the process of knowledge translation (Michie et al, ) and to the integration of EBP (McCluskey and Cusick, ; Lee and Kielhofner, ; Murphy and Robinson, ). Therefore, it is integral that, prior to undertaking knowledge translation initiatives, the barriers and learning needs of the healthcare profession in question are assessed (Grimshaw et al, ; Hakkennes and Dodd, ).…”
Section: Discussionmentioning
confidence: 94%
“…All participants strongly agreed that OTs need to be proactive in terms of VR, revisit their fundamental skills and reassert themselves as key leaders in the field of VR (Alsop, 2004;Bade and Eckert, 2008;College of Occupational Therapists, 2008;Lee and Kielhofner, 2009;World Federation of Occupational Therapists, 2012). A lack of system supports (relating to management, professional organization, legislative backing) was cited as a primary barrier to the integration of EBP and VR in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the identification of self-recognised occupational performance problems appears to enhance client motivation and to increase the relevance of personalised goals in rehabilitation. 17 , 18 ) However, there is no single tool to assess the degree of shared power between the client and the occupational therapist in the client-centric decision-making process. Therefore, it is, by default, simply evaluated subjectively by occupational therapists at the clinical site.…”
Section: Introductionmentioning
confidence: 99%